AARDRYKSKUNDE (GEOGRAFIE) AS AANGRENSENDE WETENSKAP TOT DIE GESKIEDENIS - Combrinck, J.A. (Scientia Militaria - South African Journal of Military Studies, 2012)
Historical events are so closely related to geographical conditions, that one is unable to gain a true understanding of the former, without knowledge of the latter. Lately, an introductory chapter on the geographical conditions in a country is very often included by historians, especially in historical works of a general nature. History can furthermore not be explained without geography. Students of history must know where the borders of a state are and precisely where wars and battles have been fought. It is also a fact, though less obvious, that geographical facts greatly influenced the course of history. Even the constitutional and social developments within an established nation are dependent on both because geographical conditions can influence the nature of negotiations with other countries. All foreign relations, friendly as well as hostile, are based mainly on geography, while industrial developments are mainly (although not entirely) dependent onthat which is published in geography books.